Patient outcomes and experience of a task-shared screening and brief intervention service for problem substance use in South African emergency centres: a mixed methods study - van der Westhuizen, C.; Malan, M.; Naledi, T.; Roelofse, M.; Myers-Franchi, Bronwyn; Stein, D.J.; Lahri, S.; Sorsdahl, K. (BMC, 2021)
Background: Screening, brief intervention and referral to treatment (SBIRT) programmes have resulted in generally positive outcomes in healthcare settings, particularly for problem alcohol use, yet implementation is hampered by barriers such as concerns regarding the burden on healthcare professionals. In low-resourced settings, task-sharing approaches can reduce this burden by using non-professional healthcare workers, yet data are scarce regarding the outcomes and acceptability to patients within a SBIRT service. This study aims to evaluate patient-reported outcomes, patient acceptability, perceived benefits and recommendations for improving a task-shared SBIRT service in South African emergency centres (ECs).